Brown Tumor in Parathyroid Adenoma Mimicking Malignant Bone Tumor: A Case Report - Asri Dhea Pratiwi; Setiawati, Rosy (Jember Medical Journal, 2024)
Brown tumors, also recognized as osteitis fibrosa cystica or osteoclastoma, represent a unique pathological entity intricately linked to hyperparathyroidism. Although benign in nature, brown tumor can manifest as focal bone abnormalities, presenting diagnostic challenges due to their striking resemblance to malignant bone tumors, particularly bone metastases. A 24-year-old woman presented with a lump on her left knee and right lower leg pain. Imaging unveiled multiple osteolytic lesions resembling aggressive bone tumors. Subsequent investigations, including abdominal USG, thyroid USG, bloodwork, and parathyroid hormone assessment, confirmed hyperparathyroidism with elevated PTH levels and nephrocalcinosis. HistoPA examination shows a brown tumor diagnosis, prompting parathyroidectomy. Brown tumor can mimic aggressive bone tumors both in clinical and radiological findings. Besides PTH level, thyroid and abdominal USG should be performed to find both parathyroid mass and nephrocalcinosis as the result of hypercalcemia. A HistoPA examination shoud be performed to diagnose the main cause of hyperparathyroidism, that is mostly parathyroid adenoma. As for the treatment, medical and surgical intervention can be done to treat hyperparathyroidism and brown tumor itself. Brown tumors pose a diagnostic challenge due to their association with hyperparathyroidism and their resemblance to aggressive bone tumors. Further research is needed to enhance diagnostic and therapeutic strategies for brown tumors associated with hyperparathyroidism.